The dynamics of Trooz Glacier, Antarctic Peninsula, by satellite remote sensing data - Kadurin, S.; Kadurin, V. (Ukrainian Antarctic Journal, 2023)
The paper studies the ice cover of the Trooz Glacier, Kyiv Peninsula, West Antarctic Peninsula. The main goal of the work is to study the velocity dynamics of various parts of the Trooz Glacier in 2016–2022 based on remote sensing data and to compare them with changes in meteorological variables. The glacier’s velocity was determined using 7-year data from the Copernicus Sentinel-1 satellite system based on the offset tracking technique. The characteristics of climatic changes during the same time intervals were determined according to the POWER project from NASA. To analyze the velocity field of the Trooz Glacier over time, 100 control points were selected along the entire valley from the mouth to the upland of the tributaries. For these points, values of the glacier velocity were calculated every 12 days for seven years, from 23.11.2015 to 28.12.2022. The entire glacier valley was divided into subclusters with their own average surface velocities and accelerations. To determine the level of climate change’s influence on the velocities of different parts of the Trooz Glacier, we used the method of cross-correlation. The ice flow reacted to climatic changes with a certain delay. Annual velocity fluctuations of various parts and a slight glacier movement acceleration from 2015 to 2022 were identified. The latter amounted to 7–9% of the 2016-year speed. At the same time, only in the terminus area during the studied period was there a slight slowdown in the average annual velocity detected from 2.25 m day–1 in 2016 to 2.1 m day–1 in 2022. The most intensive climatic parameters affect the middle and lower parts of the Trooz Glacier. Among the main parameters, the near-surface environment temperature can be seen as the most influential force. Temperature changes impact the glacier velocity within the first 12 to 36 days; the effect can appear later with lag intervals of up to 120 days. The role of environmental temperature is significant for the middle part of the glacier, where its valley becomes wide. For the lower part and terminus region of the glacier, the temperature effect is most significant, with the reaction of the ice flow to temperature changes occurring in the coming days. Shortwave solar radiation and ultraviolet index were also established as influencers, but only for the lower and middle glacier parts, with a lag from 12 to 48 days. The influence of the precipitation amount was the most detectable only in the lower part of the glacier.